2015
DOI: 10.1074/jbc.m114.629873
|View full text |Cite
|
Sign up to set email alerts
|

Protein Kinase A Rescues Microtubule Affinity-regulating Kinase 2-induced Microtubule Instability and Neurite Disruption by Phosphorylating Serine 409

Abstract: Background: MARK2 and PKA are both involved in the regulation of microtubule stability. Results: PKA significantly inhibits MARK2 by phosphorylating serine 409 and rescues MARK2-induced microtubule instability and neurite disruption. Conclusion: PKA functions as an upstream inhibitor of MARK2 by directly interacting and phosphorylating it. Significance: The results identify a novel interaction between PKA and MARK2, providing new insight into the signal networks of both.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…Overexpression of MARK 2/4 inhibited the activities of both CRTC2 and to a lesser extent CRTC3 ( Fig 6A ). Despite the presence of a consensus PKA phosphorylation site at S409 ( Fig 6B ), which has been reported to modulate MARK2 activity [ 35 ], phospho-mimetic and phospho-incompetent mutations at S409 had no effect on MARK2-mediated phosphorylation of CRTC2/3 at sites II and III ( Fig 6C ). We confirmed that S409 is indeed phosphorylated in response to Fsk stimulation by using a phospho-PKA substrate antibody ( Fig 6D ).…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…Overexpression of MARK 2/4 inhibited the activities of both CRTC2 and to a lesser extent CRTC3 ( Fig 6A ). Despite the presence of a consensus PKA phosphorylation site at S409 ( Fig 6B ), which has been reported to modulate MARK2 activity [ 35 ], phospho-mimetic and phospho-incompetent mutations at S409 had no effect on MARK2-mediated phosphorylation of CRTC2/3 at sites II and III ( Fig 6C ). We confirmed that S409 is indeed phosphorylated in response to Fsk stimulation by using a phospho-PKA substrate antibody ( Fig 6D ).…”
Section: Resultsmentioning
confidence: 91%
“…cAMP has been reported to inhibit SIKs and other AMPK family members through PKA-mediated phosphorylation [ 1 , 35 ]. Indeed, exposure to Fsk decreased endogenous CRTC2 and CRTC3 phosphorylation at sites II and III ( Fig 5A ).…”
Section: Resultsmentioning
confidence: 99%
“…It has been demonstrated that active MARK2 interacted with tau and phosphorylated tau at Ser262 in stably transfected cell line, while the interaction between MARK2 and tau was significantly reduced when MARK2 was inhibited by protein kinase inhibitor [25]. The overexpression of MARK2 led to hyperphosphorylation of MAPs and disturbance in microtubule array, resulting in cellular morphological changes and cell death in Chinese hamster ovary (CHO) cells [1926], while knockdown of MARK2 expression using siRNA contributed to the formation of multiple axon like neurites and elongation of axons in hippocampal neurons [2627]. One study reported that MARK2 and PTEN-induced kinase 1 (PINK1) were co-localized with mitochondrial and regulate their transport, and MARK2 was identified as an upstream regulator of PINK1 [28].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that NMDAR activated protein kinase A (PKA) which phosphorylated MARK2 [29]. MARK2 could regulate microtubule stability, neurite outgrowth, and early phosphorylation of tau in AD [26]. The augmented interactions between MARK2 and tau in AD brain suggest that MARK2 plays an important role in the early phosphorylation of tau in AD, indicating it as a potential therapeutic target.…”
Section: Discussionmentioning
confidence: 99%
“…There are four members of the Par1/MARK family in mammals. Par1/MARK plays an instrumental role in regulating various cellular processes in the brain including neuronal migration [2224], neurite outgrowth [25], dendritic spine formation, and plasticity [2631]. However, whether and how Par1 affects microglia function has yet to be explored.…”
Section: Introductionmentioning
confidence: 99%